Genome-Wide Identification and Characterization of Amino Acid Polyamine Organocation Transporter Family Genes Reveal Their Role in Fecundity Regulation in a Brown Planthopper Species (Nilaparvata lugens) - Yue, Lei; Guan, Ziying; Zhong, Mingzhao; Zhao, Luyao; Pang, Rui; Liu, Kai (Frontiers in Physiology, 2021)
The brown planthopper (Nilaparvata lugens Stål, BPH) is one of the most destructive pests of rice crops worldwide. As a sap-feeding insect, the BPH is incapable of synthesizing several amino acids which are essential for normal growth and development. Therefore, the insects have to acquire these amino acids from dietary sources or their endosymbionts, in which amino acid transporters play a crucial role by enabling the movement of amino acids into and out of insect cells. In this study, a common amino acid transporter gene family of amino acid/polyamine/organocation (APC) was identified in BPHs and analyzed. Based on a homology search and conserved functional domain recognition, 20 putative APC transporters were identified in the BPH genome. Molecular trait analysis showed that the verified BPH APC family members were highly variable in protein features, conserved motif distribution patterns, and exon/intron organization. Phylogenetic analysis of five Hemiptera insects revealed an evolutionary pattern of interfamily conservation and lineage-specific expansion of this gene family. Moreover, stage- and tissue-specific expression analysis revealed diverse expression patterns in the 20 BPH APC transporter genes. Lastly, a potential BPH fecundity regulatory gene of NlAPC09 was identified and shown to participate in the fecundity regulation through the use of quantitative polymerase chain reaction and RNA inference experiments. Our results provide a basis for further functional investigations of APC transporters in BPH.